2015
DOI: 10.1176/appi.neuropsych.15080212
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Implicit and Explicit Bias: Implications for Clinicians

Abstract: FIGURE 1. Cultural stereotypes are used to infer information about an individual based on how they are categorized. Prejudices and biases derived from the applied stereotype may result in predictable changes in behavior (i.e., discrimination). The stereotype content model systematizes stereotypes along the social judgment dimensions of warmth and competence. 1-5 The dimension of warmth rates intentions (benevolent, malevolent) and provides a basis for inferring whether someone will be a friend or enemy. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 60 publications
1
4
0
1
Order By: Relevance
“…This is sometimes compounded by the paradoxical implicit and explicit stigmatizing attitudes held by professional caregivers (nurses, doctors, social workers; Lauber et al, 2006 ; Gaebel et al, 2011 ; Stuart et al, 2012 ; Henderson et al, 2014 ; Lebowitz and Ahn, 2014 ; Oliveira et al, 2020 ) towards the very people they are supposed to help and treat (Gaebel et al, 2015 ). Stigma held by professionals is usually reflected in physician-patient communication, optimism regarding treatment options, and prediction of the chance of recovery (see Peris et al, 2008 ; Wahl, 2012 ; Reihl et al, 2015 ; Haque et al, 2021 ). Interestingly, Loch et al ( 2013 ) concluded that psychiatrists become increasingly stigmatized towards their patients as they become more familiar with the clinical features of the illness they are treating (also see Weiner et al, 1988 ).…”
Section: About Stigma Stigmatizing Attitudes and Stigmatizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is sometimes compounded by the paradoxical implicit and explicit stigmatizing attitudes held by professional caregivers (nurses, doctors, social workers; Lauber et al, 2006 ; Gaebel et al, 2011 ; Stuart et al, 2012 ; Henderson et al, 2014 ; Lebowitz and Ahn, 2014 ; Oliveira et al, 2020 ) towards the very people they are supposed to help and treat (Gaebel et al, 2015 ). Stigma held by professionals is usually reflected in physician-patient communication, optimism regarding treatment options, and prediction of the chance of recovery (see Peris et al, 2008 ; Wahl, 2012 ; Reihl et al, 2015 ; Haque et al, 2021 ). Interestingly, Loch et al ( 2013 ) concluded that psychiatrists become increasingly stigmatized towards their patients as they become more familiar with the clinical features of the illness they are treating (also see Weiner et al, 1988 ).…”
Section: About Stigma Stigmatizing Attitudes and Stigmatizationmentioning
confidence: 99%
“…Consistent with this view, Loughman and Haslam ( 2018 ) suggested that a crucial element in the fight against mental health-related stigma is public communication that “emphasizes complexity over reduction, and plasticity over fixity”. A key lesson gained from research in social neuroscience is that categorization (or labeling), based on fundamental cues such as sex, race, and age, as well as other outwardly signs, or stereotypes (e.g., facial aesthetics and expression, or tattoos and dress style), may be activated in an automatic manner, enabling appraisal and evaluation of the subject, and shaping of the behavior by the perceiver (Macrae and Bodenhausen, 2000 ; Reihl et al, 2015 ; Comte et al, 2016 ). Therefore, examination of whether and how perceptions are subject to modulation (manipulation) would seem to be a worthwhile undertaking in the future.…”
Section: What Might Neuroscience Research Contribute To Understanding...mentioning
confidence: 99%
See 1 more Smart Citation
“…Stratégies pour améliorer la reconnaissance et la gestion des biais[11][12][13][14] les étudiant•e•s à comprendre l'existence des biais et leur impact, basée sur des connaissances en psychologie cognitive, et une mise en pratique par des exercices tels que les tests d'association implicite et des ateliers de mise en situation, pour intégrer la reconnaissance et la gestion des biais 14. …”
unclassified
“…Negative perceptions of individuals with BPD among mental health care providers have potential to impact both access to care and quality of treatment provided. [29][30][31][32][33] For example, erroneous common beliefs (e.g., treatment resistance, need for resource intensive treatment plans) may create significant barriers to care. 33 Research indicates that more severe symptoms at baseline do not impair treatment response, and may actually promote better outcomes.…”
mentioning
confidence: 99%